PEMANFAATAN VIRTUAL BOX DALAM PRAKTIKUM EXTERIOR ROUTING MENGGUNAKAN BGP4 - Fati Gratianus Nafiri Larosa (Universitas Methodist Indonesia, 2017)
Today the Internet is very large network that one routing protocol cannot handle the task update the routing table of all routers. This make the Internet divided into Autonomous System (AS) is consist of many networks and many routers under the authority of a single administration. Routing inside AS is called Interior Routing Protocol. Routing between AS is called Exterior Routing Protocol. The Border Gateway Protocol version 4 (BGP4) is the Exterior Routing Protocol used in the Internet today. In this paper, five AS’s interconnection practising use a virtualized environment, that is Oracle VM Virtual Box. Ten routers uses Mikrotik RouterOS 5.25 on Virtual Box to interconnect five AS’s using the BGP, OSPF and RIP.